2021
DOI: 10.3389/fimmu.2021.678744
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells in the BBB Disruption After Acute Ischemic Stroke: Targets for Immune Therapy?

Abstract: Blood-Brain Barrier (BBB) disruption is an important pathophysiological process of acute ischemic stroke (AIS), resulting in devastating malignant brain edema and hemorrhagic transformation. The rapid activation of immune cells plays a critical role in BBB disruption after ischemic stroke. Infiltrating blood-borne immune cells (neutrophils, monocytes, and T lymphocytes) increase BBB permeability, as they cause microvascular disorder and secrete inflammation-associated molecules. In contrast, they promote BBB r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
165
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 332 publications
(366 reference statements)
0
165
0
6
Order By: Relevance
“…In previous studies, LMR was reported to be a marker of clinical progression [24], disease complications and poor outcome [25] in acute ischemic and hemorrhagic stroke, but not in the chronic phase of the disease. The temporal trend of immune cells infiltrating the brain, and their peripheral variations have been recently reviewed [26], even if studied mostly in animal models. Neutrophils, monocytes, and lymphocytes increased in the ischemic hemisphere in just a few hours, and could be found locally for 15-30 days after the ischemic event.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, LMR was reported to be a marker of clinical progression [24], disease complications and poor outcome [25] in acute ischemic and hemorrhagic stroke, but not in the chronic phase of the disease. The temporal trend of immune cells infiltrating the brain, and their peripheral variations have been recently reviewed [26], even if studied mostly in animal models. Neutrophils, monocytes, and lymphocytes increased in the ischemic hemisphere in just a few hours, and could be found locally for 15-30 days after the ischemic event.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate effects of ischemic injury are induced by the reduction of cerebral blood flow, oxygen, and nutrients, leading to cell death via necrosis and apoptosis in the ischemic core region. During this process, danger-associated molecular patterns (DAMPs), which include high mobility group box-1 (HMGB1) and peroxiredoxin family proteins, are released to activate brain resident microglial cells by pattern recognition receptors (PRRs), including toll-like receptors (TLRs) and initiate leukocyte transmigration, by secreting interleukin (IL)-1, IL-6, matrix metallopeptidase (MMP)-9, and tumor necrosis factor (TNF)α [30,[37][38][39][40][41]. In the periphery of the ischemic core, called the penumbra, neurons may survive and provoke pathogenic factors, including calcium overload, oxidative stress, and glutamate excitotoxicity, that can cause more cell death [30].…”
Section: Ischemic Strokementioning
confidence: 99%
“…Stroke is a devastating cerebrovascular disease, containing two types: ischemic stroke (IS) and hemorrhagic stroke (HS). Accounting for approximately 80% of all cases, ischemic stroke is the most common subtype, which is triggered by arterial embolization or thromboembolism in the cerebrum [ 1 ]. A wide range of clinical manifestations of IS includes physical disability, impaired cognitive and emotional abilities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%